Are “Genetic Enhancements” Really Enhancements? - Shickle, Darren (Cambridge quarterly of healthcare ethics, 2000)
The word enhancement is value laden and potentially misleading in the context of genetics. Dictionary definitions of enhance include “increase in value,” “improve,” “appreciate,” and “inflate.” The term genetic enhancement would be better replaced with a more neutral term such as “genetic manipulation” to reflect the fact that the consequences of as yet largely untried technology may be beneficial, balanced, or harmful. The aim of this paper is to highlight some of the potential negative consequences of the use of “enhancing technology” and hence to challenge whether “enhancements” are actually always enhancements. Thus it is necessary to question whether what may appear to be a new means of enhancement may not actually result in any significant change or is less effective than existing means of enhancement; may actually make things worse; or may on some measures actually make some things better, but on other measures or in other senses make things worse (either for the person being enhanced or for others).